التعارض بين قاعدة التطهير من الدفوع وقاعدة الحيازة في المنقول سند الملكية - الأعرجي، أمير صلاح نصر (جامعة الكوفة - كلية القانون, 2020)
تعتبر الورقة التجارية مالا منقولا وتنتقل بواسطة التظهير أو المناولة اليدوية إذا كان التظهير للحامل أو على بياض وتارة ينشأ السند مباشرة لحامله كما هو الحال في الشيك على بياض وفي بعض الأحيان يفقد المالك الأصلي حيازة السند لحامله بواقعة معينة ويتم تظهيره بعد ذلك لشخص يجهل ضياعه يسمى الحائز حسن النية فيطالب كل منهما بملكية السند فينشأ نزاع بين المالك الأصلي الذي فقد السند والحائز الذي وصل إليه السند. وقد عالج القانون التجاري مسألة ضياع السند لحامله ووصوله للحائز في المادة (56) وكذلك القانون المدني في المادة (1164)‏ ‏وقد تعارض حكمهما حول ملكية السند فالمادة (56) تقر بملكية الحائز على وفق ضوابط معينة والمادة (1164) تقر بملكية المالك الأصلي على وفق ضوابط معينة أيضا. إن أنواع التظهير من حيث الشكل ثلاث اسمي وللحامل وعلى بياض. فإذا كان التظهير اسميا يخرج من نطاق التعارض ذلك أن الورقة سيتحدد مالكها مباشرة ولا يمكن منازعته. وبالتالي لا يثير ضياعها نزاعا حول ملكيتها ولكن الخطورة تكمن في ضياع الورقة المظهرة للحامل أو على بياض والتي يطلق عليها السند لحامله ويدخل في نطاق التعارض منها الحوالة التجارية والكمبيالة المظهرتان تظهيرا تمليكيا أو توثيقيا للحامل أو على بياض. والشيك المظهر تظهيرا تمليكيا لحامله فقط. ويحل التعارض بتطبيق قاعدة التطهير من الدفوع على السند لحامله الذي يدخل في نطاق التعارض فيما يخص ضياعه ووصوله للحائز على وفق الضوابط المنصوص عليها في هذه القاعدة ويجب أيضا أن يكون التظهير صحيحا ومستجمعا لشروط صحته من حيث الشكلية والرضا والمحل والسبب وبناء على ما تقدم تكون ملكية السند لحامله الضائع للحائز وليس للمالك الأصلي الذي فقد الحوالة. كما إن قاعدة الحيازة في المنقول سند الملكية تطبق في الحالات الآتية: إذا ظهرت الورقة التجارية وكان تظهيرا للحامل أو على بياض ووصلت إلى حامل حسن النية وكان التظهير باطلا. وكذلك تطبق على كل ما يخرج عن مفهوم السند لحامله الداخل في دائرة التعارض. وأيضا إذا كان التظهير توكيليا. وكذلك تظهير الشيك تظهيرا تأمينيا. وإذا وقع التظهير بعد ميعاد التقديم وبعد عمل الاحتجاج. A commercial paper is considered movable money and is transferred by endorsement or manual handling if the endorsement of the bearer or blank and sometimes the bond is created directly to the bearer, as in the blank check. Sometimes the original owner loses possession of the bond to the bearer in a certain event and is then endorsed for someone who is unaware of his loss called the holder. The commercial law has addressed the issue of the loss of the bond to the bearer and its access to the holder in Article 56, as well as the Civil Code in Article 1164. Their judgment is inconsistent with the ownership of the bond, omen Article (56) recognizes the ownership of the award in accordance with certain rules and Article (1164) recognizes the ownership of the original owner in accordance with certain controls as well. The types of endorsement in terms of form are three nominal and for the pregnant and blank, if the nominal endorsement comes out of the scope of the conflict because the paper will be determined by the owner directly and can not be disputed, and therefore does not provoke a loss of ownership dispute, but the danger lies in the loss of the paper showing the pregnant or blank, which is called It has the bond of the bearer and falls within the scope of the conflict, including the commercial transfer and the bill of exchange, appearing a proprietary or documentary manifestation of the bearer or blank, and the check appearance is a proprietary manifestation of the bearer only. The conflict shall be resolved by the application of the cleansing of defenses rule on the bond to the bearer, which falls within the scope of the conflict with respect to its loss and access to the holder in accordance with the rules set forth in this rule. The endorsement must also be valid and summarized for the conditions of health in terms of formality, satisfaction, place and reason, The lost holder of the holder and not the original owner who lost the transfer. The rule of tenure in the movable title deed is applied in the following cases: If the commercial paper appears and was a manifestation of the holder or blank and reached the holder of good faith and the endorsement is void, as well as applied to everything that deviates from the concept of the deed to the holder in the conflict, and also if The endorsement is a power of attorney, as well as the endorsement of the check as an insurance endorsement, and if the endorsement occurs after the submission date and after the protest action.
Keywords: السندات الملكية -- حقوق الملكية -- الأوراق التجارية -- الحقوق العينية